Measuring outpatient resource use and case mix in ophthalmology in north east England. Issue 4 (April 1998) - McNamee, P; Parkin, D; Allen, D; Steen, N; Hutchinson, A
Abstract : OBJECTIVES: To test the extent to which two existing ambulatory case mix measures (Ambulatory Visit Groups and Ambulatory Patient Groups) and other variables can explain resource use variations in ophthalmic outpatient visits. DESIGN: Three week prospective study of three consultant outpatient clinics. SETTING: One ophthalmic hospital (Sunderland Eye Infirmary, Sunderland, Tyne and Wear) and three outreach clinics (South Tyneside District Hospital, South Shields, Tyne and Wear; Dryburn Hospital, Durham, Co Durham; and Hartlepool General Hospital, Hartlepool, Cleveland). SUBJECTS: 325 patients who visited ophthalmic outpatient clinics. MAIN OUTCOME MEASURES: Mean consultation time and mean cost distributions by case mix group, analysed by analysis of variance. RESULTS: Ambulatory case mix measures can explain some of the variation in resource use for outpatient visits, but different measures differ in the extent to which they can do so. Clinicians' behaviour also accounts for a significant amount of such variation. Simpler measures of visit type, without diagnostic or procedure information, do not explain resource use variations. CONCLUSIONS: Existing measures perform reasonably well, but their data requirements may preclude their introduction in the National Health Service. Caution is required in advocating simpler measures, however. The influence of clinical practice on resource use variations is important; in this study, most differences between clinicians were not attributable to differences in case mix.